Freshwater and brackish bryozoan species of Croatia (Bryozoa: Gymnolaemata, Phylactolaemata) and their genetic identification - Franjević, Damjan; Novosel, Maja; Koletić, Nikola (Zootaxa, 2015)
Freshwater and brackish species of bryozoans belong to the Phylactolaemata and Gymnolaemata class. Twelve species of bryozoans were recorded and morphologically determined at eight locations in the Black Sea and the Adriatic basin in Croatia. Twelve species of Bryozoa have been listed in the taxonomic index for Croatia (Conopeum seurati, Lophopus crystallinus Paludicella articulata, Cristatella mucedo, Fredericella sultana, Hyalinella punctata, Plumatella casmiana, Plumatella emarginata, Plumatella fruticosa, Plumatella fungosa, Plumatella geimermassardi and Plumatella repens). For the purposes of gene identification of recorded species, molecular markers for nuclear 18S and 28S genes, ITS2 region and mitochondrial COI gene were amplified. Genetic identifications of morphologically determined bryozoan species were confirmed using highly similar sequences local alignment analysis. Proliferation of freshwater bryozoan species over long distances with the help of the vector animals was confirmed by defining haplotypes on the base of 18S, 28S and ITS2 sequences associated with the Black Sea-Mediterranean waterfowl flyway.